(untitled) (Research, Society and Development, 2023)
This study aimed to identify in the literature the perception of health professionals about the insertion of medical students in Primary Health Care. For this, an integrative literature review was carried out, following the steps: Identification of the problem; Literature search; Data Analysis and Conclusion. Initially, 490 articles were obtained, and there were no duplicates. After reading the title and abstract, 443 articles were excluded, including 47 articles, which were read in full. Of these, 34 documents were excluded, as they did not respond to the study’s guiding question. Thus, 10 articles were included in this study. From the analysis of the articles, three categories emerged: I - The context in which the curricular internship in medicine was carried out; II - Perceptions of the health team, patients and students in relation to the curricular internship III - Challenges for the performance and well-being of the medical student during the curricular internship. Finally, it is understood that the context of Primary Health Care is essential for the training of medical students, as it is a conducive environment for undergraduates to have contact with practice from the first months of graduation and because it provides them with a full contact with patients.